2019
DOI: 10.1038/s41598-019-54722-w
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the preservation effect of canagliflozin on pancreatic beta cell mass using SPECT/CT imaging with 111In-labeled exendin-4

Abstract: Radiolabeled exendin derivatives are promising for non-invasive quantification of pancreatic beta cell mass (BCM); longitudinal observation of BCM for evaluation of therapeutic effects has not been achieved. The aim of this study is to demonstrate the usefulness of our developing method using [Lys12(111In-BnDTPA-Ahx)]exendin-4 to detect longitudinal changes in BCM. We performed a longitudinal study with obese type 2 diabetes model (db/db) mice administered canagliflozin, which is reported to preserve BCM. Six-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…In db/db mice, longitudinal in vivo SPECT observations revealed a spontaneous reduction in pancreatic probe uptake (35, 103) and that diet-restriction attenuated the reduction in BCM loss (35). In vivo SPECT observations also observed that canagliflozin (a sodium glucose transporter-2 inhibitor) and DS-8500a (a G protein-coupled receptor 119 agonist) attenuated the progression of BCM loss in db/db mice (34,103). Although chronic hyperglycemia might affect probe uptake via changes in GLP-1R expression levels on the b-cell membrane surface (110), the pancreatic uptake of [Lys 12 ( 111 In-BnDTPA-Ahx)]exendin-4 in SPECT images could replicate the BCM relationship among these model mice with different glycemic states (35,102,103).…”
Section: Application Of Glp-1r-targeted Imaging In Diabetes Mellitusmentioning
confidence: 93%
See 2 more Smart Citations
“…In db/db mice, longitudinal in vivo SPECT observations revealed a spontaneous reduction in pancreatic probe uptake (35, 103) and that diet-restriction attenuated the reduction in BCM loss (35). In vivo SPECT observations also observed that canagliflozin (a sodium glucose transporter-2 inhibitor) and DS-8500a (a G protein-coupled receptor 119 agonist) attenuated the progression of BCM loss in db/db mice (34,103). Although chronic hyperglycemia might affect probe uptake via changes in GLP-1R expression levels on the b-cell membrane surface (110), the pancreatic uptake of [Lys 12 ( 111 In-BnDTPA-Ahx)]exendin-4 in SPECT images could replicate the BCM relationship among these model mice with different glycemic states (35,102,103).…”
Section: Application Of Glp-1r-targeted Imaging In Diabetes Mellitusmentioning
confidence: 93%
“…In vivo SPECT observations also observed that canagliflozin (a sodium glucose transporter-2 inhibitor) and DS-8500a (a G protein-coupled receptor 119 agonist) attenuated the progression of BCM loss in db/db mice (34,103). Although chronic hyperglycemia might affect probe uptake via changes in GLP-1R expression levels on the b-cell membrane surface (110), the pancreatic uptake of [Lys 12 ( 111 In-BnDTPA-Ahx)]exendin-4 in SPECT images could replicate the BCM relationship among these model mice with different glycemic states (35,102,103). Moreover, the pancreatic uptake of [Lys 12 ( 111 In-BnDTPA-Ahx)]exendin-4 maintained a linear correlation with histological BCM, even among diabetic and non-diabetic RCS-10 mice (11).…”
Section: Application Of Glp-1r-targeted Imaging In Diabetes Mellitusmentioning
confidence: 93%
See 1 more Smart Citation
“…In order to solve this issue, pancreatic b-cell-specific imaging using nuclear medicine techniques has been developed in recent years (7)(8)(9)(10)(11). In particular, radioisotope-labeled probes using exendin peptidesincluding glucagon-like peptide-1 receptor (GLP-1R) agonist and antagonist-have been promising for positron emission tomography (PET) and single-photon emission computed tomography (SPECT) imaging (12)(13)(14), which enabled mouse pancreas imaging, its image analysis for BCM quantification (15,16), and investigation of the protective effect of pancreatic b cells on anti-diabetic treatment (17,18). In addition, these probes were shown to be useful for the detection of insulinoma (13).…”
Section: Introductionmentioning
confidence: 99%
“…Exendin-4 can also be used to monitor endogenous BCM evolution in mice after drug intervention. Thus, after nine weeks of canagliflozin treatment (a sodium-glucose transporter-2 inhibitor), an increase in BCM and accumulation of [Lys 12 ( 111 In-Bn-diethylenetriaminepenta-acetic acid(DTPA)-Ahx)]exendin-4 was observed in mice [ 59 ]. The same probe was also used to assess the protective effect of DS-8500a (a novel G protein-coupled receptor-119 agonist) on BCM in db / db mice, a model of severe insulin resistance and diabetes [ 60 ].…”
Section: Bcm Probes Presently Under Clinical Investigationmentioning
confidence: 99%